The Effect of Milking Techniques on Escherichia coli Contamination in Cow's Milk in Jember - Suswati, Enny; Nadhiva, Alvien Zahrotun; Rumastika, Nindya Shinta (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Milk is a highly nutritious food but easily contaminated by bacteria. Those bacterias could be pathogenic. Staphylococcus aureus, Escherichia coli, and Salmonella sp. are pathogenic microorganisms. Milk contamination which occurs during the milking process can come from various sources such as cow skin, udder, water, soil, dust, humans, equipment, and air. Escherichia coli is a fecal contamination indication. and the possibility of enteropathogenic or toxigenic microorganisms so E. coli is known as a causative agent for diarrhea and foodborne illness. Milking machine usage can reduce the total plate count, maintain udder health, and cow nipples, and improve milk yield, milk quality, and udder health. Indonesian dairy farming still does a lot of milking by hand. The aim of the study was to determine the differences in E. coli contamination in cow milk because of modern milking and traditional milking techniques in Jember Regency. This is observational analytic research using a cross-sectional design with a total sample of 26. The study was conducted in December 2018. Contamination of E. coli in milk was tested using the MPN method, confirmation test using EMB, and Gram staining. Data analysis using bivariate analysis with chi-square test. The results of the study found E. coli contamination in 84.6% of modern milking techniques and 100% of traditional techniques. The conclusion of the study was that E. coli contamination in cow's milk because of traditional milking techniques was greater than that of modern milking techniques, but the results were not significantly different.